vault backup: 2025-02-18 09:36:10
This commit is contained in:
parent
c63861e8f4
commit
0e758ef864
@ -122,7 +122,15 @@ $$ \dfrac{d}{dx}(\dfrac{f(x)}{g(x)}) = \dfrac{f'(x)g(x) -f(x)g'(x)}{(g(x))^2} $
|
||||
$$ \dfrac{d}{dx} e^x = e^x $$
|
||||
$$ \dfrac{d}{dx}a^x = a^x*(\ln(a)) $$
|
||||
for all $a > 0$
|
||||
# Logarithms
|
||||
|
||||
For natural logarithms:
|
||||
$$ \dfrac{d}{dx} \ln |x| = \dfrac{1}{x} $$
|
||||
|
||||
For other logarithms:
|
||||
$$ \dfrac{d}{dx} \log_a x = \dfrac{1}{(\ln a) x}$$
|
||||
When solving problems that make use of logarithms, consider making use of logarithmic properties to make life easier, eg:
|
||||
$$ \ln(\dfrac{x}{y}) = \ln(x) - \ln(y) $$
|
||||
# Chain Rule
|
||||
$$ \dfrac{d}{dx} f(g(x)) = f'(g(x))*g'(x) $$
|
||||
## Examples
|
||||
|
Loading…
x
Reference in New Issue
Block a user